Evaluation of structural and microscopic properties of tetragonal ZrO2 for the facet coating of 980 nm semiconductor laser diodes. (16th February 2015) - Dixit, V K; Marathe, A; Bhatt, G; Khamari, S K; Rajiv, K; Kumar, R; Mukherjee, C; Panchal, C J; Sharma, T K; Oak, S M
Abstract: ZrO2 based antireflection coatings are expected to show a high laser induced damage threshold in the facet coating applications of laser diodes. A single layer of undoped ZrO2 and multilayers of ZrO2 /SiO2 are deposited at 80 °C by an e-beam evaporation technique on GaAs and Si substrates. ZrO2 layers deposited under the optimized conditions are of a tetragonal nature and the grain size increases with reduced atomistic configuration mismatch between the surfaces of the layer and substrate. The electron/optical density profiles of the tetragonal ZrO2 single layer and multilayers of ZrO2 /SiO2 are obtained from x-ray reflectivity measurements which confirm a uniform surface without any evidence of interfacial diffusion. The refractive index spectrum of tetragonal ZrO2 is found to be different from its other stable monoclinic allotropes. This is due to the possible differences in the atomistic structure of tetragonal ZrO2 that might be caused by oxygen vacancies and impurities. The measured values of refractive index, surface and interface roughness are used to engineer the layer structures for achieving 2 and 90% reflectivity at 980 nm at the front and the rear facets of laser diodes. The slope efficiency of the facet coated laser diode increases from 0.5 to 0.91 W A −1 without any measurable difference in the threshold current density.